Analysis of intrinsic elements in the novel Ketika Cinta Bertasbih by Habiburrahman El Shirazy - Erlina, Erlina (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to analyze the intrinsic elements in the novel Ketika Cinta Bertasbih by Habiburrahman El Shirazy using a structuralist approach supported by literary psychology. The elements examined include theme, characterization, setting, plot, and moral values that build the narrative structure of the novel. This research employs a qualitative descriptive method. The primary data source is the novel Ketika Cinta Bertasbih (2007). Data were collected through close reading, note-taking, and classification of relevant textual evidence and analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings show that the novel highlights themes of struggle, love, and Islamic spirituality. The main character is portrayed as religious, responsible, and hardworking, while the setting reinforces Islamic cultural values. Overall, the novel reflects strong moral and religious messages that are relevant to daily life.